Geographical analysis of the frequency of rainy days remaining for more than two days in stations (Baghdad, Al-Amarah and Al-Hay) - Talib Abbas Karim / Saddam Razzaq Abboud ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The study depended on determining the number of continuous rainy days in which more than two days were registered in thr0ee climatic stations (Baghdad, Al-Amarah, and Al-Hay) during the rainyseasons (2009-2020), the study turned out that the replication is on the increase in allstation, where during the rainfall it tends to decrease in Baghdad's station as well as Al-Amarah's station, but it is towards increase in Al-Hay's station, Baghdad's station registered higher repetition in continuous rainy days than a couple of days, nearly 44 repetitions, The total of continuous rainy days was 158 days, as well as the rainfall registered during the repetition of continuous rainy days in which it rained for more than two days was nearly (1010.8) millimeters, the study explored that through surface and upper map monitoring in low pressure areas, atmospheric depression was the most influential depression in increasing the duration of the rain wave and the continuation of rain for more than two days during the study period.DOI /10.54633/2333-021-042-010